How to iGuide: flat panel detector, CT-assisted, minimally invasive evacuation of intracranial hematomas. (11th October 2021) - Dornbos III, David; Halabi, Cathra; DiNitto, Julie; Mueller, Kerstin; Fiorella, David; Cooke, Daniel L; Arthur, Adam S
Abstract : Evidence is growing to support minimally invasive surgical evacuation of intraparenchymal hematomas, particularly those with minimal residual hematoma volumes following evacuation. To maximize the potential for neurologic recovery, it is imperative that the trajectory for access to the hematoma minimizes disruption of normal parenchyma. Flat panel detector CT-based navigation and needle guidance software provides a platform that uses flat panel detector CT imaging obtained on the angiography table to aid reliable and safe access to the hematoma. In addition to providing a high degree of accuracy, this method also allows convenient and rapid re-imaging to assess navigation accuracy and the degree of hematoma evacuation prior to procedural completion. We provide a practical review of the syngo iGuide needle guidance software and the methodology for incorporating its use, and the software of other vendors, in a variety of minimally invasive methods for evacuation of intraparenchymal hematomas.